Not theories but explanations? A methodological inquiry - Hammersley, Martyn (Theory and society, 2025)
[...]there are those who deny the value of theory altogether (see, for instance, Winch, 1958 and Hutchinson et al., 2008). [...]even social scientists who insist on its importance differ sharply in their views of it. More broadly, at the end of one dimension is what we might call the positivist conception of science, according to which a theory identifies a universal law that explains why some type of event occurs under specified conditions; while at the other end is what Fay (1975:110) called ‘the critical model of social science’, which holds that ‘a social theory does not simply offer a picture of the way that a social order works; instead, a social theory is itself a catalytic agent of change within the complex of social life which it analyses’. [...]even among those for whom producing theoretical knowledge, rather than changing the world, is the social scientific goal, there have been divergent views about the form it should take (for instance, identifying causal mechanisms versus scientific laws) as well as recurrent complaints, from diverse directions, about the failure properly to develop it, and about the speculative character of much of it (see Glaser & Strauss, 1967, Willer & Willer, 1973, Rule, 1997). Marx’s work offers an integrated series of concepts – labour power, use and exchange value, exploitation, social class divisions, etc. – that, it is claimed, can serve as an effective means of understanding capitalism, and is relevant in seeking to understand any aspect of modern social life, from industrial organisation to art and religion. [...]I suggest, the main focus ought to be on developing and testing explanatory theories and explanations. Besides theoretical frameworks that shape the research questions addressed, there are also ontological and epistemological assumptions built into the use of particular methods for producing data and analysing it.